Spirituality and religiosity: challenges and possibilities into medical practice (Research, Society and Development, 2023)
Objective: To conduct a review of scientific productions about what the challenges and possibilities are to integrate spirituality and religiosity (S/R) into medical practice. Method: This is an integrative literature review in the period between 2017 to 2023 in English, Portuguese and Spanish languages. The search was carried out in the Virtual Health Library using the descriptors: “Spirituality”, “Medicine”, “Medical History Taking”, “Medical Education”, “Religion”, “Religion and Medicine”. Results: Twelve articles were selected and their contents were classified into two categories: Challenges of incorporating S/R approach in Clinical Practice, and Possibilities of S/R implementation in Medical Service. It is evident, among listed studies, that the dichotomy between challenges and possibilities traverses questions such as knowledge, training, interest, beliefs, location and time. Final Considerations: It has been evidenced that, in spite of the considerable recognition of the importance of the subject, there is a scarcity of literature knowledge along with both conceptual and practice interest among medical professionals, as well as a lack of scientific production focused on the clinical practice of spirituality and religiosity. As it constitutes a fundamental aspect of integral care, it is necessary for the available tools to be better integrated in the areas of education and medical service.